Regulatory Compliance and Risk Management in Pharmaceuticals and Healthcare - Nwoke, Judith (International Journal of Health Sciences, 2024)
Purpose: This study aims to examine the evolving regulatory landscape and its impact on compliance and risk management within the pharmaceutical and healthcare industries. It seeks to identify effective strategies for maintaining data integrity and traceability in accelerated pharmaceutical development (APD), and to understand how these strategies improve patient care and healthcare system responsiveness. Methodology: The research involves a comprehensive review of current regulations, emerging trends, and industry practices. It utilizes an analysis of regulatory updates, risk management frameworks, and case studies to illustrate successful compliance strategies and the challenges faced by organizations. Findings: The study highlights key regulatory requirements, identifies common risks and mitigation strategies, and provides insights into effective practices for ensuring data integrity and traceability. It demonstrates that robust compliance and risk management practices contribute to enhanced patient outcomes and improved healthcare system efficiency. Unique Contribution to Theory, Policy, and Practice: This research offers a detailed examination of the intersection between regulatory compliance and risk management, providing a valuable framework for understanding and addressing the complexities of the pharmaceutical and healthcare sectors. It contributes to theory by integrating recent regulatory changes with practical risk management approaches, informs policy by highlighting critical areas for regulatory focus, and offers actionable recommendations for industry practitioners to optimize compliance and data management processes.